Performance Analysis of Building-Embedded Loop Antenna Systems for Smart City IoT Networks - Farhan Rezki Arifin; Nurmayanti Zain; Lompo Ramos Emakarim (Universitas Darul Ulum, 2025)
The increasing demand for seamless connectivity in Smart City environments has encouraged the integration of communication systems directly within building infrastructures. This study presents the performance analysis of a building-embedded loop antenna system designed for sub-GHz Internet of Things (IoT) applications. The proposed antenna, made of stainless steel and embedded in a reinforced concrete column, was modeled and simulated using Ansys HFSS (High Frequency Structure Simulator) based on the Finite Element Method (FEM). Analytical and full-wave simulations were conducted to evaluate key electromagnetic parameters, including return loss, voltage standing wave ratio (VSWR), impedance bandwidth, and radiation characteristics. The results showed that the antenna achieved resonance at 700 MHz with a return loss of –20.95 dB and a VSWR of 1.196, demonstrating excellent impedance matching. The impedance bandwidth covered 563–939 MHz, ensuring compatibility with various IoT protocols such as LoRaWAN, NB-IoT, Z-Wave, and ZigBee. Despite reduced gain due to dielectric absorption and coupling within the concrete medium, the antenna maintained an omnidirectional radiation pattern, suitable for low-power IoT nodes. These findings indicate that building-embedded loop antennas can function as integrated communication elements while preserving architectural integrity.